December 2021 Pulmonary Case of the Month: Interstitial Lung Disease with Red Knuckles - Lewis J. Wesselius MD (Arizona Thoracic Society, 2021)
No abstract available. Article truncated after 150 words. History of Present Illness A 56-year-old man was referred for a second opinion on recent onset of diffuse parenchymal lung disease. He had started noting mild dyspnea with yard work approximately in March 2021. His symptoms progressed over the next month with increasing shortness of breath and some fever. He presented to outside emergency department on April 17, 2021 and chest CT showing patchy ground-glass opacities with some areas of irregular consolidation (Figure 1). He was subsequently seen by an outside pulmonologist and started empirically on prednisone (50 mg/day). An outside lung biopsy had been performed which showed nonspecific interstitial pneumonitis. There was some improvement in his symptoms and his prednisone dose was reduced to 20 mg/day; however, his symptoms subsequently worsened with saturations noted to drop to 85% with any ambulation. He also had swelling of his left face and a biopsy of the parotid gland with the findings …